2009
DOI: 10.1007/s10750-008-9697-1
|View full text |Cite
|
Sign up to set email alerts
|

The input of foraminiferal infaunal populations to sub-fossil assemblages along an elevational gradient in a salt marsh: application to sea-level studies in the mid-Atlantic coast of North America

Abstract: The suitability of marsh sites for sea-level studies was examined based on a field study along a transect from high to low marsh. Living foraminifera at Bombay Hook (Delaware, USA) are considered to be shallow infaunal (i.e., uppermost 10 cm). Peak concentrations were found at 1-10 cm in the high marsh, 1-5 cm in the intermediate marsh, and 3-5 cm in the low marsh. However, sporadic deep infaunal inputs in the low marsh could significantly contribute to the sub-fossil assemblage. In the upper 10 cm buried (dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Live specimens were more abundant at shallow depths, and their abundance decreased with increasing depth. This distribution appears to indicate that the optimum depth for live T. salsa is the top 10 cm of sediment, which is similar to the distribution of many other foraminiferal species throughout the world that normally inhabit this depth range (Goldstein and others, 1995;Ozarko and others, 1997;Hippensteel and others, 2000;Leorri and Martin, 2009).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Live specimens were more abundant at shallow depths, and their abundance decreased with increasing depth. This distribution appears to indicate that the optimum depth for live T. salsa is the top 10 cm of sediment, which is similar to the distribution of many other foraminiferal species throughout the world that normally inhabit this depth range (Goldstein and others, 1995;Ozarko and others, 1997;Hippensteel and others, 2000;Leorri and Martin, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…Biological staining techniques are used to label live individuals and appropriately include or exclude them from analyses (e.g., Patterson and others, 2000;Edwards and others, 2004; Barbosa and others, 2005). In addition, some studies need to identify an appropriate cm-sampling depth that best represents the proportion of live and dead individuals within a given modern assemblage for later comparison with fossil assemblages (e.g., Goldstein and Harben, 1993;Leorri and Martin, 2009). Bernhard (2000) reviewed a wide variety of possible techniques for identifying live versus dead foraminifera.…”
Section: Introductionmentioning
confidence: 99%
“…Most paleoenvironmental studies of intertidal marshes use the foraminiferal assemblages in surface sediment (upper 1 to 2 cm) as a modern counterpart assuming that they are characterized primarily by epifaunal production (e.g., Scott and Medioli, 1980;Gehrels, 1994;de Rijk, 1995;Horton, 1999;Patterson et al, 2004;Woodroffe et al, 2005;Kemp et al, 2009a) or shallow infaunal (Buzas et al, 1993). However, several studies have shown that intertidal foraminifera can live infaunally as deep as several decimeters in some marsh settings (e.g., Goldstein et al, 1995;Ozarko et al, 1997;Goldstein and Watkins, 1998;Saffert and Thomas, 1998;Goldstein and Watkins, 1999;Patterson et al, 1999;Hippensteel et al, 2002;Culver and Horton, 2005;Duchemin et al, 2005;Tobin et al, 2005;Berkeley et al, 2007;Leorri and Martin, 2009;Milker et al, 2015a). In such cases sampling the uppermost surface sediment (0-1 cm) would produce poor modern analogues (Duchemin et al, 2005).…”
Section: Surficial Vs Subsurface Foraminiferamentioning
confidence: 99%
“…Furthermore, it has implicit assumptions about the nature of foraminiferal populations including infaunal habitation (e.g. Goldstein and Harben, 1993;Ozarko and others, 1997;Goldstein and Watkins, 1998;Patterson and others, 1999;Horton and Murray, 2006;Leorri and Martin, 2009), seasonal and inter-annual variability (e.g. Buzas and others, 2002;Hippensteel and others, 2002;Horton and Murray, 2006;Berkeley and others, 2008;Martin and others, 2009) and small-scale (meter) spatial patterns, termed patchiness (Buzas, 1968;Swallow, 2000;Morvan and others, 2006).…”
Section: Introductionmentioning
confidence: 99%